2009
DOI: 10.1007/s12029-009-9085-8
|View full text |Cite
|
Sign up to set email alerts
|

Cholangiocarcinoma in Primary Sclerosing Cholangitis

Abstract: We review latest recommendations about screening strategies to enable the early detection of CCA in PSC, using CA 19-9 and ultrasound imaging, as well as fluorescent in situ hybridization techniques to enhance the accuracy of biliary cytology. We also review the emerging role of liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 72 publications
0
10
0
1
Order By: Relevance
“…CA-125 is detectable in up to 65% of patients with CC 38 40. In a chemotherapy trial setting, a raised baseline CA-125 was found to be prognostic for survival 37.…”
Section: Diagnosismentioning
confidence: 94%
See 1 more Smart Citation
“…CA-125 is detectable in up to 65% of patients with CC 38 40. In a chemotherapy trial setting, a raised baseline CA-125 was found to be prognostic for survival 37.…”
Section: Diagnosismentioning
confidence: 94%
“…CA19-9 does not discriminate between CC, pancreatic or gastric malignancy and may also be elevated in severe hepatic injury from any cause. Furthermore, 10% of individuals lack Lewis antigen and cannot produce CA19-9 36–38 40…”
Section: Diagnosismentioning
confidence: 99%
“…As the second most common primary hepatic malignancy, its incidence and mortality rates are increasing worldwide in recent decades (Khan et al 2005;Ustundag and Bayraktar 2008;Mosconi et al 2009). Many risk factors contribute to CCA development, including primary sclerosing cholangitis (Abbas and Lindor 2009), congenital biliary cystic diseases, liver cirrhosis, and viral infections (Su et al 1997), exposed thorotrast and nitrosamine (Mitacek et al 1999a;Lipshutz et al 2002), and parasitic liver diseases such as Opisthorchis viverrini (OV) and Clornorchis sinensis (IARC 1994;Kim et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Cholangiocarcinoma is reported to occur in 8 -13.2 % of those with PSC [5,7], with an annual incidence of 1.5 % per year [39] and is often fatal, with 5 year survival rates of less than 10 % [19,41]. It can develop within the liver and common bile duct, but is most frequently identified at the hilar region [7].…”
Section: Complications Cancermentioning
confidence: 99%